Modelling of suspension and motoring force for bearingless permanent magnet synchronous motor - Mamat, Normaisharah (2015)
Bearingless permanent magnet synchronous motor (PMSM) is the combination of the characteristic of conventional permanent magnet synchronous motor with magnetic bearing. It is a kind of high performance motor because having both advantages of PMSM and magnetic bearing such as no friction, high speed and long operating life. It is also suitable for high speed application such as compressor, turbines and pump. The purpose of this research is to modelling of motoring torque and suspension force for bearingless permanent magnet synchronous motor by using Maxwell 2D of ANSYS Finite Element Method (FEM). The designed bearingless PMSM consist of two sets of stator winding namely motoring torque winding and suspension force winding. Bearingless PMSM is developed by using the method of suspension force and the mathematical model of electromagnetic torque and suspension force. This mathematical model is built by using Simulink/Matlab and the other parameter values such as current, voltage, airgap length and force are identified. The relationship among configuration of windings, radial suspension force and current are complicated, so finding these relationship is important for modelling the bearingless PMSM. The final suspension force result obtained is compared between FEM and Matlab. Then by using Matlab, the controller for bearingless PMSM is developed to realize the controllable of rotor that consist of position controller and speed controller. This research covered the principle of suspension force, the mathematical model, Proportional Intergral (PI) control system of bearingless PMSM and also FEM analysis. Finally, the recommendation for future research studies is included to improve the research on bearingless PMSM.